The Medication Safety Adventure Trail: An Educational Intervention to Promote Public Awareness on Medication Safety - Audrey Flornoy-Guédon; Liliane Gschwind; Antoine Poncet; Pierre Chopard; Caroline Fonzo-Christe; Pascal Bonnabry (Pharmacy)
Engaging patients in medication safety is essential but remains under-addressed in hospital settings. This pilot study aimed to assess the impact of an educational intervention—the Medication Safety Adventure Trail—on medication safety knowledge and satisfaction among hospital visitors. A quasi-experimental pre-post intervention using this educational tool was conducted over five days. A booth was set up in a hospital lobby inviting all passers-by to follow a six-step trail involving riddles to solve. The experiment comprised three phases: 1. Briefing plus pre-test; 2. The trail; 3. Debriefing plus post-test. A logistic mixed-effects model was employed to assess changes in the odds of correct responses to eight items between the pre-test and post-test. A five-point scale assessed participants’ degrees of certainty (DC) in their answers, and a comparison pre- and post-test was performed with a linear mixed-effects model. Satisfaction was based on Kirkpatrick’s levels 1 and 2 (reaction and learning) and was assessed using categorical scales and open-ended questions. A total of 93 participants completed the trail (60% non-healthcare professionals, 36% healthcare professionals, and 4% unspecified). The odds of a correct answer were higher at post-test than at pre-test (72% vs. 51%, p < 0.001), and the odds of providing a correct answer were nearly five times higher following the activity compared to before (OR = 4.8 [95%CI 3.5 to 6.4], p < 0.001). The mean DC was also improved from pre-test to post-test (4.43, 95%CI [4.36–4.49] vs. 4.83, 95%CI [4.80–4.86]; p < 0.001). All 93 participants reported being either very satisfied (89%) or satisfied (11%) with the educational tool. The tool significantly improved participants’ knowledge about medication safety issues and was appreciated.